Peran Kajian Kitab Kuning di Masjid Ushuluddin dalam Pengembangan Masyarakat Rowolaku Kajen - Faidatul Khusna; sabbihhisma, Iqna; Prameswari Bono, Shafa Ajeng; Nafila, Akmala; QOmariyah (Journal of Islamic Management, 2026)
In the context of modernization and globalization, society faces significant challenges in maintaining authentic religious values relevant to contemporary life. This study aims to analyze the role of classical Islamic text studies at the Ushuluddin Rowolaku Kajen Mosque in developing the surrounding community’s religious, social, and cultural life. Using a qualitative field research approach, this study explores the traditional routine of classical Islamic text learning that has been practiced since the 1950. The Ushuluddin Rowolaku Kajen Mosque thus serves as a center for both religious learning and community transformation, preserving Islamic scholarly traditions while responding to contemporary social changes.